2016
DOI: 10.1080/23322039.2016.1258810
|View full text |Cite
|
Sign up to set email alerts
|

Economic growth, financial development and trade openness in Nigeria: An application of the ARDL bound testing approach

Abstract: For over a decade now, various efforts have been put in place by various governments of the developing economies to promote economic growth, financial development and expand trade with mixed results. The ability of financial development and/or trade openness to influence economic growth in the developing economies has been a subject of hot debate and remains inconclusive. While a number of scholars are of the view that compelling cointegration exists among each of these constructs, another set of substantial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 61 publications
4
69
3
2
Order By: Relevance
“…The results of this study show that international trade plays a significant role in the economic growth of Cote d'Ivoire, validating the trade-led growth hypothesis both in the short and long run. This finding accords with Asfaw (2014), Zarra-Nezhad et al (2014), and Brueckner and Lederman (2015), but contradicts with Vlastou (2010), Polat et al (2015), Ulaşan (2015), Were (2015) and Lawal et al (2016) who reported a negative or insignificant impact of trade openness on economic growth. Some of these studies do not include into the analysis capital or labor as additional explanatory variables.…”
Section: Unit Root and Cointegration Testscontrasting
confidence: 43%
See 1 more Smart Citation
“…The results of this study show that international trade plays a significant role in the economic growth of Cote d'Ivoire, validating the trade-led growth hypothesis both in the short and long run. This finding accords with Asfaw (2014), Zarra-Nezhad et al (2014), and Brueckner and Lederman (2015), but contradicts with Vlastou (2010), Polat et al (2015), Ulaşan (2015), Were (2015) and Lawal et al (2016) who reported a negative or insignificant impact of trade openness on economic growth. Some of these studies do not include into the analysis capital or labor as additional explanatory variables.…”
Section: Unit Root and Cointegration Testscontrasting
confidence: 43%
“…Polat et al (2015) find that trade openness impedes economic growth in South Africa. Finally, Lawal, Nwanji, Asaleye, and Ahmed (2016) apply the ARDL methodology to Nigeria and find a negative long-run impact of trade openness on economic growth but a positive growth effect in the short run. Further, a two-way causality was found between the two variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sakyi, Commodore, and Opoku (2015) investigated the long-run impact of FDI and trade openness on economic growth in Ghana and found that the interaction of FDI and exports has been crucial in fostering growth. A study by Lawal et al (2016) found a two-way causality between trade openness and growth as well as a negative and positive effect in the long and short run respectively. The study applied the ARDL methodology in Nigeria.…”
Section: Agriculture Industry Servicesmentioning
confidence: 99%
“…where m → ∞, ℎ + → + and ℎ − → + are the dynamic adjustment patterns. However, a rise in openness to trade improves the development of the financial sector at a 5% level of significance, just as documented in the study of Lawal et al (2016b). Meanwhile, C02 emission has a positive relationship with financial development, which means that; as the financial development of Algeria improves, the quality of the environment as well gets more deteriorated.…”
Section: Long-run Estimatementioning
confidence: 91%